Comparison of four cholesterol-based stationary phases for the separation of steroid hormones - Soukup, Jan; Bocian, Szymon; Jandera, Pavel; Buszewski, Bogusław (WILEY-VCH, 2014)
The chromatographic behavior of steroid hormones on four cholesterol-bonded stationary phases with different structures in binary methanol/water mobile phases was studied. Of the stationary phases tested, the commercially available stationary phases Cogent UDC cholesterol and COSMOSIL cholester provided better separations of steroid hormones in comparison to homemade aminocholesterol and diaminocholesterol stationary phases. The results show that the temperature has a significant influence on the retention and selectivity for steroid hormones separation. The temperature increase may cause changes in the elution order. From the dependences of the retention (ln k) on temperature (1/T), the standard partial molar enthalpy and standard partial molar entropy were calculated and their enthalpic and entropic contributions to the retention were compared. The enthalpic effects principally control the retention mechanism.
Srovnání čtyř stacionárních fází na bázi cholesterolu pro separaci steroidních hormonů
Keywords: cholesterol-bonded phase; enthalpy; entropy; retention; steroid hormones; stacionární fáze; cholesterol; steroidní hormony; separace